Pengaruh Harga Dan Kualitas Layanan Terhadap Loyalitas Pelanggan: (Studi Pada Pelanggan Ahass Surakarta) - Hellen Cahya Permata; Pemilia Sulistyowati (MANAJEMEN, 2025)
Analyzing the effects of price and service quality on customer loyalty among research participants at AHASS Surakarta was the aim of this study. This study's main goal was to determine whether pricing and service quality significantly or concurrently affect consumer loyalty. Using a quantitative approach, this study involved 68 respondents who were active participants. Data analysis was conducted using multiple regression analysis, supported by instrument validity and reliability tests and classical assumptions to ensure model stability. The results showed that price has a significant impact on customer loyalty, with price consistency that matches the value received by customers increasing their engagement with the service. Service quality also proved to have a significant influence, particularly in terms of punctuality, friendliness, and mechanical reliability, which provided a positive experience for customers. Simultaneously, price and service quality contributed significantly to building customer loyalty, confirming the importance of these two factors as a company's strategy in retaining its customer base.